Konflik Sosial dan Alternatif Pemecahannya - Parsudi Suparlan (Antropologi Indonesia, 1999)
In this article the author looks into social conflict and alternative solutions to the problem. He begins by discussing the merits of a conflict model in viewing society, as expounded by Dahrendorf, bailey, and others. The author argues that, in contrast, the New Order Regime of Indonesia followed a model of equilibrium , characteristic of most pseudo-democratic or authoritarian states...[...] the author suggest that with a conflict model, differences are given, and conflict give rise to competition where there exist rules for competition that are fair and well-enforced. These ruled must be enforced b and impartial police. However, the incorporation of the police into the Indonesian military for the past 32 years has placed emphasis on the use of military tactics for resolving conflicts. In fact, one solution to the problem of conflict is the presence of one institution or organization that can be trusted and depended upon by all partied involved; and this should be the police.